The association among dominant tree species in mount Halimun Salak National Park. Issue 1 (May 2021) - Denny,; Setyawati, T; Kalima, T; Wardani, M; Zuraida,; Fambayun, R A; Susilo, Adi
Abstract: Association is a relationship in an ecosystem between living organisms. Positive associations arise when a plant species is associated with other plant species, and negative associations occur under opposite situations. This study aimed to identify the relationship among dominant tree species of the National Park Mount Halimun Salak by producing a permanent 100 m × 100 m plot divided into 25 sub-plots of 20 m × 20 m to store the trees. Smaller sizes of 5 m × 5 m and 1 m × 1 m were nested on each sub-plot to inventory saplings and seedlings. Vegetation research determined the dominant tree species. In addition to an association coefficient, the Association indexes were determined by a contingency table of 2 × 2. The results showed that the composition of vegetation at the tree levels includes 32 families, 46 genera and 61 species; 28 families, 35 genera and 53 species at sapling stage; 24 families with 19 genera and 43 species at the seedling level. The dominant species on the tree level were Altingia excelsa, Schima walichii, Agathis damara, Engelhardia spicata on the sapling level were Schima walichii, Altingia excelsa, Litsea sp., Macaranga triloba on the seedling level were Schima walichii, Aporosa frutescens, Quercus sundaica, Macaranga triloba . The association analysis showed that Agathis damara and Altingia excelsa as well Agathis damara and Engelhardia spicata were very significantly associated negatively.